Solitary Laryngeal Metastasis from Transitional Cell Carcinoma of the Kidney: Clinical Case and Review of the Literature - Tarek Assi; Elie El Rassy; Amine Haddad; Joseph Kattan (Case Reports in Otolaryngology)
The urogenital tract is a rare origin of laryngeal metastasis; transitional cell carcinoma with laryngeal metastases had never been reported previously. In this paper, we describe the clinical and pathological characteristics, evolution, and treatment of the first reported case of a laryngeal metastasis of a TCC followed by a brief review of the literature.